Komunikasi Lintas Budaya pada Tayangan Youtube UENO Family - Najih Farihanto, Muhammad (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the institutional communication transformation of Ahmad Dahlan University (UAD) through the implementation of the PESO Media (Paid, Earned, Shared, Owned) model and social media marketing strategies in the new student admissions process from a sociological perspective, particularly in building public trust. The research method used was a qualitative approach with a case study design. Data collection techniques included structured and semi-structured interviews with new student admissions administrators, participant observation, and analysis of UAD's official social media content. The results indicate that the implementation of the PESO Media model at UAD is carried out in an integrated manner, with Paid Media playing a role in increasing initial reach and visibility, Earned Media strengthening the institution's credibility through collaboration with students, lecturers, alumni, and content creators, while Shared Media fosters a culture of public participation through active audience engagement, and Owned Media serves as the central narrative control center and the institution's official information source. Consistent and creative implementation of social media marketing strategies has been proven to build emotional connections, increase brand awareness, and foster trust among prospective students. The conclusion of this study confirms that the strategic integration of the PESO Media model and social media marketing not only represents a transformation of UAD's institutional communication but also reflects a sociological shift toward a participatory, collaborative, and trust-based communication culture in the context of higher education. Keywords: Institutional Communication, PESO Media, Social Media Marketing, Student Admissions, Public Trust